The Poetics of Perspective - Elkins, James 1955- (Cornell University Press, 2018)
Perspective has been a divided subject, orphaned among various disciplines from philosophy to gardening. In the first book to bring together recent thinking on perspective from such fields as art history, literary theory, aesthetics, psychology, and the history of mathematics, James Elkins leads us to a new understanding of how we talk about pictures. Elkins provides an abundantly illustrated history of the theory and practice of perspective. Looking at key texts from the Renaissance to the present, he traces a fundamental historical change that took place in the way in which perspective was conceptualized; first a technique for constructing pictures, it slowly became a metaphor for subjectivity. That gradual transformation, he observes, has led to the rifts that today separate those who understand perspective as a historical or formal property of pictures from those who see it as a linguistic, cognitive, or epistemological metaphor. Elkins considers how the principal concepts of perspective have been rewritten in work by Erwin Panofsky, Hubert Damisch, Martin Jay, Paul Ricoeur, Jacques Lacan, Maurice Merleau-Ponty, and E. H. Gombrich. The Poetics of Perspective illustrates that perspective is an unusual kind of subject: it exists as a coherent idea, but no one discipline offers an adequate exposition of it. Rather than presenting perspective as a resonant metaphor for subjectivity, a painter's tool without meaning, a disused historical practice, or a model for vision and representation, Elkins proposes a comprehensive revaluation. The perspective he describes is at once a series of specific pictorial decisions and a powerful figure for our knowledge of the world